Protection and Exchange of Personal Data on the Web in the Registry of Civil Status - Liridon Hoti; Kastriot Dermaku; Selami Klaiqi; Hiflobina Dermaku (Ital Publication, 2023)
Personal data are widely consumed by the central civil registry using interconnection systems as web services and by other institutions that use the data to deliver services. Therefore, the risks of misuse of personal data are major concerns, thus the need for protection and security by improving personal data reliability. This paper analyzes the links between the Central Registry of Civil Status and other institutions and the security of the links by providing data protection and security during communication with web services. This paper emphasizes privacy in information technology and explores modern challenges for every legal entity and natural person. The protection of personal data in related institutions is discussed. The case study concerns the interconnections between the Central Registry of Civil Status in the Republic of Kosovo and other systems in data exchange institutions, such as the modern part of e-government. For data collection, a questionnaire was administered at the institution responsible for the central civil registry to evaluate the protection of personal data and the connection with other institutions from which such personal data originate and are consumed. This paper has also studied the level of applying cryptographic security methods to protect personal data. Doi: 10.28991/ESJ-2023-07-01-03 Full Text: PDF